Nitazoxanide: A Drug Repositioning Compound with Potential Use in Chagas Disease in a Murine Model - Minerva Arce-Fonseca; Rodolfo Andrés Gutiérrez-Ocejo; José Luis Rosales-Encina; Alberto Aranda-Fraustro; Juan José Cabrera-Mata; Olivia Rodríguez-Morales (MDPI AG, 2023)
Chagas disease (ChD), caused by Trypanosoma cruzi, is the most serious parasitosis in the western hemisphere. Benznidazole and nifurtimox, the only two trypanocidal drugs, are expensive, difficult to obtain, and have severe side effects. Nitazoxanide has shown to be effective against protozoa, bacteria, and viruses. This study aimed to evaluate the nitazoxanide efficacy against the Mexican T. cruzi Ninoa strain in mice. Infected animals were orally treated for 30 days with nitazoxanide (100 mg/kg) or benznidazole (10 mg/kg). The clinical, immunological, and histopathological conditions of the mice were evaluated. Nitazoxanide- or benznidazole-treated mice had longer survival and less parasitemia than those without treatment. Antibody production in the nitazoxanide-treated mice was of the IgG1-type and not of the IgG2-type as in the benznidazole-treated mice. Nitazoxanide-treated mice had significantly high IFN-γ levels compared to the other infected groups. Serious histological damage could be prevented with nitazoxanide treatment compared to without treatment. In conclusion, nitazoxanide decreased parasitemia levels, indirectly induced the production of IgG antibodies, and partially prevented histopathological damage; however, it did not show therapeutic superiority compared to benznidazole in any of the evaluated aspects. Therefore, the repositioning of nitazoxanide as an alternative treatment against ChD could be considered, since it did not trigger adverse effects that worsened the pathological condition of the infected mice.